A Randomized Trial of a Dedicated Bifurcation Stent Versus Provisional Stenting in the Treatment of Coronary Bifurcation Lesions - Généreux, Philippe; Kumsars, Indulis; Lesiak, Maciej; Kini, Annapoorna; Fontos, Géza; Slagboom, Ton; Ungi, Imre; Metzger, D. Christopher; Wykrzykowska, Joanna J.; Stella, Pieter R.; Bartorelli, Antonio L.; Fearon, William F.; et al. (Journal of the American College of Cardiology, 2015)
Bifurcation lesions are frequent among patients with symptomatic coronary disease treated by percutaneous coronary intervention. Current evidence recommends a conservative (provisional) approach when treating the side branch (SB). The TRYTON (Prospective, Single Blind, Randomized Controlled Study to Evaluate the Safety & Effectiveness of the Tryton Side Branch Stent Used With DES in Treatment of de Novo Bifurcation Lesions in the Main Branch & Side Branch in Native Coronaries) bifurcation trial sought to compare treatment of de novo true bifurcation lesions using a dedicated bifurcation stent or SB balloon angioplasty. We randomly assigned patients with true bifurcation lesions to a main vessel stent plus provisional stenting or the bifurcation stent. The primary endpoint (powered for noninferiority) was target vessel failure (TVF) (cardiac death, target vessel myocardial infarction, and target vessel revascularization). The secondary angiographic endpoint (powered for superiority) was in-segment percent diameter stenosis of the SB at 9 months. We randomized 704 patients with bifurcation coronary lesions at 58 centers (30 from Europe and 28 from the United States). At 9 months, TVF was 17.4% in the bifurcation stent group compared with 12.8% in the provisional group (p = 0.11), mainly because of a higher periprocedural myocardial infarction rate (13.6% vs. 10.1%, p = 0.19). The TVF difference of +4.6% (2-sided 95% confidence interval: −1.0 to 10.3; upper limit of the 1-sided 95% confidence interval: 10.3) was not within the pre-specified noninferiority margin of 5.5% (p = 0.42 for noninferiority). The SB in-segment diameter stenosis among the angiographic cohort was lower in the bifurcation stent group compared with the provisional group (31.6% vs. 38.6%, p = 0.002 for superiority), with no difference in binary restenosis rates (diameter stenosis ≥50%) at 9 months follow-up (22.6% vs. 26.8%, p = 0.44). Provisional stenting should remain the preferred strategy for treatment of non–left main true coronary bifurcation lesions. (Prospective, Single Blind, Randomized Controlled Study to Evaluate the Safety & Effectiveness of the Tryton Side Branch Stent Used With DES in Treatment of de Novo Bifurcation Lesions in the Main Branch & Side Branch in Native Coronaries [TRYTON]; NCT01258972)